Composite material for preventing peritoneal dialysis catheter outlet infection and preparation method and application thereof
By covering the antibacterial coating of Cu2+/TA/HAP/CS composite on the peritoneal dialysis catheter, the problems of catheter outlet infection and peritonitis were solved, significantly reducing the infection rate and drug resistance, and improving the therapeutic effect.
Patent Information
- Application Number
- CN202411483803.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The frequency of infections in the peritoneal dialysis catheter outlet is high, resulting in peritonitis and treatment failure, affecting the health and medical quality of patients. The existing technology is difficult to effectively prevent the formation of bacterial biofilms and drug resistance.
Cu2+/TA/HAP/CS composite material is used as the antibacterial coating, and the outer surface of the catheter is covered with copper ion/tanninic acid/hydroxyapatite/chitosan composite material through electrophoretic deposition technology to prevent the formation and enhancement of bacterial biofilms. Antibacterial properties.
It significantly reduces the incidence of peritonitis, effectively prevents the formation of bacterial biofilms, improves the antibacterial performance of the catheter, reduces bacterial resistance, and improves the treatment effect and quality of life of patients.
Smart Images

Figure CN118987365B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of clinical medicine, and in particular relates to a composite material for preventing peritoneal dialysis catheter outlet infection, and a preparation method and application thereof. Background Art
[0002] Chronic renal failure is a type of disease caused by a variety of chronic kidney diseases that leads to the deterioration of renal function. It is characterized by a long course of disease, difficulty in treatment and rehabilitation, poor prognosis, multiple complications, and irreversible renal damage. The main clinical manifestations of patients are acid-base and water-electrolyte imbalance, metabolic dysfunction, and retention of metabolites. Chronic renal failure often affects all systems in the body, causing functional damage to different organs and electrolyte disorders, which seriously affect the patient's daily work and life. Certain treatments must be taken, otherwise they will face the continuous trouble of uremia. At present, the main treatment options for chronic renal failure are hemodialysis, peritoneal dialysis (PD) and kidney transplantation.
[0003] In PD, it is very important to use a well-functioning catheter because the catheter may be related to the incidence of peritonitis, the efficiency of dialysis, and the overall quality of treatment, which is one of the main obstacles to the optimal use of PD. Peritoneal dialysis catheter-related infections include peritoneal dialysis catheter outlet infection and tunnel infection. As the dialysis time of peritoneal dialysis patients increases, the incidence of peritoneal dialysis catheter-related infections increases. The 3-year infection rate of peritoneal dialysis is as high as 70%, of which about 40% progress to peritonitis, and 15% require the removal of the peritoneal dialysis catheter due to infection, which greatly affects the treatment effect of patients and threatens their life and health. Catheter-related infection (CRI) is one of the most common hospital-acquired infections at present, leading to increased mortality and morbidity, greatly affecting the quality of medical care and patient health. Avoiding infection when the catheter is implanted in the human body has become a common clinical problem. Biofilms formed by bacterial colonization are the main cause of catheter-related infections. Due to untimely dressing changes, catheter traction, and weak self-care awareness of patients, peritoneal dialysis patients are prone to peritoneal dialysis catheter outlet infection, which affects the efficiency of peritoneal dialysis and the quality of life of patients. Therefore, how to overcome the shortcomings of existing technologies is an urgent problem to be solved in the field of clinical medical technology. Summary of the invention
[0004] The purpose of the present invention is to solve the deficiencies of the prior art and to provide a composite material for preventing peritoneal dialysis catheter outlet infection and a preparation method and application thereof.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing a composite material for preventing peritoneal dialysis catheter outlet infection comprises the following steps:
[0007] Step (1), preparation of TA / HAP NPs nanoparticles: adding hydroxyapatite to a 5 mg / mL tannic acid aqueous solution, reacting under centrifugal conditions, removing the supernatant after the reaction, and then drying to obtain TA / HAP NPs nanoparticles (also called tannic acid / hydroxyapatite nanoparticles);
[0008] The mass ratio of hydroxyapatite to the volume ratio of tannic acid aqueous solution is 2:48~52g / mL;
[0009] Step (2), Cu 2+ Preparation of / TA / HAP composite material: Add the TA / HAP NPs prepared in step (1) to a 5 mg / mL copper chloride dihydrate aqueous solution, react under centrifugal conditions, remove the supernatant after the reaction, and then dry to obtain Cu 2+ / TA / HAP composite material (also known as copper ion / tannic acid / hydroxyapatite composite material);
[0010] Among them, the volume ratio of the mass of TA / HAP NPs nanoparticles to the cupric chloride dihydrate aqueous solution was 2:48~52g / mL;
[0011] Step (3), preparation of chitosan acetic acid aqueous solution: uniformly mixing acetic acid aqueous solution with a volume percentage concentration of 1% and chitosan aqueous solution with a mass percentage concentration of 1% to obtain chitosan acetic acid aqueous solution;
[0012] The volume ratio of the acetic acid aqueous solution to the chitosan aqueous solution is 8.7-9.3:1;
[0013] Step (4), Cu 2+ Preparation of / TA / HAP / CS composites: Cu 2+ The / TA / HAP composite material was added to the chitosan acetic acid aqueous solution obtained in step (3) and ultrasonically dispersed to obtain Cu 2+ / TA / HAP / CS composite EPD solution (also known as copper ion / tannic acid / hydroxyapatite / chitosan composite electrophoretic deposition solution);
[0014] Among them, Cu 2+ The volume ratio of the mass of / TA / HAP composite material to chitosan acetate aqueous solution is 0.95~1.05:1 mg / mL.
[0015] Furthermore, in step (1), the centrifugal speed is 9000-10000 rpm, and the centrifugal time is 10 min; the drying is performed by vacuum drying, the drying temperature is 70° C., the vacuum degree is 93.3-98.6 KPa, and the time is 4.5-5.5 hours.
[0016] Furthermore, in step (2), the centrifugal speed is 9000-10000 rpm, and the centrifugal time is 10 min; vacuum drying is adopted, the drying temperature is 70° C., the vacuum degree is 93.3-98.6 KPa, and the time is 4.5-5.5 hours.
[0017] Furthermore, in step (4), the frequency of ultrasonic dispersion is 20 k~100 kHz.
[0018] The present invention also provides a composite material for preventing peritoneal dialysis catheter outlet infection obtained by the preparation method of the composite material for preventing peritoneal dialysis catheter outlet infection.
[0019] The present invention also provides application of the composite material for preventing peritoneal dialysis catheter outlet infection in the preparation of a peritoneal dialysis catheter.
[0020] Furthermore, the peritoneal dialysis catheter comprises an implant tube, the implant tube comprises an intra-abdominal section, a subcutaneous section and an exposed section, the intra-abdominal section and the exposed section are respectively connected to the two ends of the subcutaneous section, and the exposed section is connected to a joint at one end away from the subcutaneous section; an inner cuff is provided at one end of the subcutaneous section close to the intra-abdominal section, and an outer cuff is provided at one end of the subcutaneous section close to the exposed section; an outer surface of the implant tube from the outer cuff to the joint and an outer surface of the joint are covered with an antibacterial coating; the antibacterial coating is made of Cu 2+ / TA / HAP / CS composite material.
[0021] Furthermore, the method for obtaining the antibacterial coating on the outer surface of the joint is as follows: a stainless steel cylindrical ring is used as an anode and a titanium alloy sheet is used as a cathode. 2+ The EPD solution of / TA / HAP / CS composites was deposited at 20 V DC voltage for 5–7 min;
[0022] The method for obtaining the antibacterial coating on the outer surface of the insertion tube is as follows:
[0023] Cu 2+ After coating with the EPD solution of / TA / HAP / CS composite material, the composite material was dried in an oven at 38℃~42℃ for 10~12h.
[0024] The present invention further provides a peritoneal dialysis catheter, comprising an implant tube, the implant tube comprising an intra-abdominal section, a subcutaneous section and an exposed section, the intra-abdominal section and the exposed section are respectively connected to two ends of the subcutaneous section, and an end of the exposed section away from the subcutaneous section is connected to a joint; an end of the subcutaneous section close to the intra-abdominal section is provided with an internal cuff, and an end of the subcutaneous section close to the exposed section is provided with an external cuff; an outer surface of the implant tube from the external cuff to the joint and an outer surface of the joint are covered with an antibacterial coating; the antibacterial coating is made of Cu 2+ / TA / HAP / CS composite material.
[0025] Furthermore, the material of the joint is titanium.
[0026] In the present invention, the EPD in the EPD solution of the composite material refers to an electrophoretic deposition technology; the EPD solution refers to a solution that can be used for electrophoretic deposition.
[0027] The invention provides an antibacterial coating on the outer surface of the external Kraft joint insertion tube and the outer surface of the joint, wherein the coating is made of hydroxyapatite (HAP), chitosan (CS), tannic acid (TA) and copper ions (Cu 2+ ) made of Cu 2+ / TA / HAP composite materials
[0028] Hydroxyapatite (HAP) is often used in trauma surgery to increase the osteoconductivity and osteointegration of titanium alloy stents because it can mimic the nanostructure and chemical composition of natural bone minerals. Chitosan has good biocompatibility, biodegradability, non-toxicity and strong antibacterial effects, making it an extremely attractive natural polymer material in the biomedical field. In addition, chitosan, as a biopolymer, has a strong film-forming ability, which means that the presence of chitosan can improve the adhesion of the composite coating; tannic acid is a polyphenolic biomolecule with good antibacterial properties; it can form stable complexes with a variety of metal ions, and then with Cu 2+ The addition of can further improve the antibacterial properties of the coating.
[0029] The experiment analyzed the antibacterial activity of tannic acid against common clinical isolates and its effect on biofilm. Nine common clinical isolates were collected: Staphylococcus aureus, Staphylococcus epidermidis, Staphylococcus haemolyticus, Enterococcus faecalis, Enterococcus faecium, Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Acinetobacter baumannii. The minimum inhibitory concentration (MIC) of various antimicrobial drugs against the above clinical strains was determined by agar dilution method. According to the results of drug sensitivity test, each clinical strain was divided into multidrug resistant (MDR) group and non-multidrug resistant (nMDR) group. Thirty strains were randomly selected from each group, totaling 540 strains, as experimental strains. The MIC values of tannic acid against the above strains were detected by agar dilution method, and the differences between the two groups were compared. Tannic acid was added to the biofilm culture medium to detect its effect on the formation of bacterial biofilm in each group. It was proved that tannic acid showed strong antibacterial activity against the nine clinical strains, among which the antibacterial activity against Staphylococcus bacteria was significantly greater than that against other bacteria (P<0.05). It is proved that tannic acid has a certain inhibitory effect on the formation of bacterial biofilm.
[0030] The present invention adopts Cu 2+When coating the / TA / HAP / CS composite material, existing coating methods can be used, for example, the titanium alloy joint is coated by EPD (Electrophoretic deposition), but it is not limited thereto. The coating thickness is preferably 0.05μm ~ 0.5μm.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] Peritonitis is one of the most common serious complications in peritoneal dialysis patients and the most important cause of technical failure or even death. The reason is that repeated bacterial infection and drug resistance occur, which are closely related to the formation of bacterial biofilm. 2+ / TA / HAP / CS composite coating.
[0033] Hydroxyapatite (HAP) is often used in trauma surgery to increase the osteoconductivity and osteointegration of titanium alloy scaffolds because it can mimic the nanostructure and chemical composition of natural bone minerals. Chitosan (CS) has good biocompatibility, biodegradability, non-toxicity and strong antibacterial effects, making it an extremely attractive natural polymer material in the biomedical field. In addition, chitosan, as a biopolymer, has a strong film-forming ability, which means that the presence of chitosan can improve the adhesion of the composite coating; tannic acid (TA) is a polyphenolic biomolecule with good antibacterial properties, and tannic acid can also form stable complexes with a variety of metal ions. Copper, as an essential trace element in the human body, has become an excellent antibacterial metal material due to its good biocompatibility, and a sufficient concentration of copper ions can kill more than 99% of bacteria within 2 hours. Titanium alloy materials with copper elements can not only kill bacteria in direct contact with the material, but also free copper ions still have a killing effect on bacteria within a certain range around them, effectively preventing the formation of bacterial biofilms. With Cu 2+ The addition of can further improve the antibacterial properties of the coating.
[0034] Peritoneal dialysis fluid has high osmotic properties such as high sugar and low pH, which undoubtedly makes it a good culture medium for bacterial growth. In addition, the peritoneal dialysis tube is made of silica gel material with strong adsorption, and Staphylococcus aureus easily forms biofilm on the surface of the peritoneal dialysis tube. Once the biofilm is formed, the bacteria are protected by the polymer matrix and successfully avoid the attack of the body's immune system and the killing of antibacterial drugs, increasing the bacterial resistance by 10 to 100 times, and can continuously release bacteria, leading to repeated attacks of peritonitis or tube removal. The present invention prepares an antibacterial coating on the outside of the peritoneal dialysis tube to cover the silica gel material, which effectively prevents the formation of bacterial biofilm and can reduce the incidence of peritonitis.
[0035] At the same time, due to the electrostatic interaction between free TA and HAP, and the phenolic hydroxyl group of TA has the ability to chelate calcium ions in HAP. 2+ After that, the remaining phenolic hydroxyl groups of TA can also chelate with it. 2+ The hydroxyl groups in HAP also have coordination effects. 2+ / TA / HAP / CS composite material particles are integrated and fixed, making the coating less likely to wear and fall off. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The front view of the peritoneal dialysis catheter of the present invention; wherein, 1, intra-abdominal segment; 2, subcutaneous segment; 3, exposed segment; 4, joint; 5, internal cuff; 6, external cuff; 7, antibacterial coating;
[0037] Figure 2 It is a top view of the connector of the peritoneal dialysis catheter of the present invention; wherein, 4, connector; 7, antibacterial coating;
[0038] Figure 3 The results of antibacterial performance test; (a) is a colony photo of Escherichia coli colonies in the Ti alloy group grown on an agar plate; (b) is a colony photo of Escherichia coli colonies in the Ti-CS group grown on an agar plate; (c) is a colony photo of Escherichia coli colonies in the Ti-CS@NP group grown on an agar plate; (d) is a quantitative statistical graph of Escherichia coli colonies in each group; (e) is a colony photo of Staphylococcus aureus colonies in the Ti alloy group grown on an agar plate; (f) is a colony photo of Staphylococcus aureus colonies in the Ti-CS group grown on an agar plate; (g) is a colony photo of Staphylococcus aureus colonies in the Ti-CS@NP group grown on an agar plate; (h) is a quantitative statistical graph of Staphylococcus aureus colonies;
[0039] Figure 4 This is a result diagram of the antibacterial activity of the coating tested using live and dead bacteria staining;
[0040] Figure 5 This is a graph showing the results of measuring the bacterial dispersion on the composite coating using live and dead bacteria staining techniques;
[0041] Figure 6 Electron microscopic comparison of the growth of mouse embryonic osteoblast precursor cells on the surface of Ti alloy group, Ti-CS group and Ti-CS@NP group;
[0042] Figure 7 Fluorescence electron microscopy comparison of cell adhesion and migration structures on the surfaces of Ti alloy group, Ti-CS group and Ti-CS@NP group. DETAILED DESCRIPTION
[0043] The present invention is further described in detail below in conjunction with embodiments.
[0044] Those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the art or the product specifications are used. If the manufacturer of the materials or equipment used is not specified, they are all conventional products that can be purchased.
[0045] Example 1
[0046] A method for preparing a composite material for preventing peritoneal dialysis catheter outlet infection comprises the following steps:
[0047] Step (1), preparation of TA / HAP NPs nanoparticles: adding hydroxyapatite to a 5 mg / mL tannic acid aqueous solution, reacting under centrifugal conditions, removing the supernatant after the reaction, and then drying to obtain TA / HAP NPs nanoparticles;
[0048] The mass ratio of hydroxyapatite to the volume ratio of tannic acid aqueous solution is 2:50 g / mL;
[0049] Step (2), Cu 2+ Preparation of / TA / HAP composite material: Add the TA / HAP NPs prepared in step (1) to a 5 mg / mL copper chloride dihydrate aqueous solution, react under centrifugal conditions, remove the supernatant after the reaction, and then dry to obtain Cu 2+ / TA / HAP composites;
[0050] Among them, the volume ratio of the mass of TA / HAP NPs nanoparticles to the cupric chloride dihydrate aqueous solution was 2:50 g / mL;
[0051] Step (3), preparation of chitosan acetic acid aqueous solution: uniformly mixing acetic acid aqueous solution with a volume percentage concentration of 1% and chitosan aqueous solution with a mass percentage concentration of 1% to obtain chitosan acetic acid aqueous solution;
[0052] The volume ratio of the acetic acid aqueous solution to the chitosan aqueous solution is 9:1;
[0053] Step (4), Cu 2+ Preparation of / TA / HAP / CS composites: Cu 2+ The / TA / HAP composite material was added to the chitosan acetic acid aqueous solution obtained in step (3) and ultrasonically dispersed to obtain Cu 2+ / TA / HAP / CS composite EPD solution;
[0054] Among them, Cu2+ The volume ratio of the mass of / TA / HAP composite material to the chitosan acetate aqueous solution was 1:1 mg / mL.
[0055] The composite material of this embodiment is used for preventing peritoneal dialysis catheter outlet infection in the preparation of peritoneal dialysis catheter. Figure 1~Figure 2 As shown, the peritoneal dialysis catheter comprises an implant tube, and the implant tube comprises an intra-abdominal section 1, a subcutaneous section 2 and an exposed section 3, wherein the intra-abdominal section 1 and the exposed section 3 are respectively connected to the two ends of the subcutaneous section 2, and the exposed section 3 is connected to a connector 4 at one end away from the subcutaneous section 2; an inner cuff 5 is provided at one end of the subcutaneous section 2 close to the intra-abdominal section 1, and an outer cuff 6 is provided at one end of the subcutaneous section 2 close to the exposed section 3; an outer surface of the implant tube between the outer cuff 6 and the connector 4 and an outer surface of the connector 4 are covered with an antibacterial coating 7; the antibacterial coating 7 is made of Cu 2+ / TA / HAP / CS composite material.
[0056] Example 2
[0057] A method for preparing a composite material for preventing peritoneal dialysis catheter outlet infection comprises the following steps:
[0058] Step (1), preparation of TA / HAP NPs nanoparticles: adding hydroxyapatite to a 5 mg / mL tannic acid aqueous solution, reacting under centrifugal conditions, removing the supernatant after the reaction, and then drying to obtain TA / HAP NPs nanoparticles;
[0059] The mass ratio of hydroxyapatite to the volume ratio of tannic acid aqueous solution is 2:48 g / mL;
[0060] Step (2), Cu 2+ Preparation of / TA / HAP composite material: Add the TA / HAP NPs prepared in step (1) to a 5 mg / mL copper chloride dihydrate aqueous solution, react under centrifugal conditions, remove the supernatant after the reaction, and then dry to obtain Cu 2+ / TA / HAP composites;
[0061] Among them, the volume ratio of the mass of TA / HAP NPs nanoparticles to the cupric chloride dihydrate aqueous solution was 2:48 g / mL;
[0062] Step (3), preparation of chitosan acetic acid aqueous solution: uniformly mixing acetic acid aqueous solution with a volume percentage concentration of 1% and chitosan aqueous solution with a mass percentage concentration of 1% to obtain chitosan acetic acid aqueous solution;
[0063] The volume ratio of the acetic acid aqueous solution to the chitosan aqueous solution is 8.7:1;
[0064] Step (4), Cu 2+ Preparation of / TA / HAP / CS composites: Cu 2+ The / TA / HAP composite material was added to the chitosan acetic acid aqueous solution obtained in step (3) and ultrasonically dispersed to obtain Cu 2+ / TA / HAP / CS composite EPD solution;
[0065] Among them, Cu 2+ The volume ratio of the mass of / TA / HAP composite material to chitosan acetate aqueous solution is 0.95:1 mg / mL.
[0066] In step (1), the centrifugal speed is 9000 rpm and the centrifugal time is 10 min. The drying is carried out by vacuum drying, the drying temperature is 70° C., the vacuum degree is 93.3 KPa, and the drying time is 4.5 hours.
[0067] In step (2), the centrifugal speed is 9000 rpm and the centrifugal time is 10 min. Vacuum drying is adopted with a drying temperature of 70° C., a vacuum degree of 93.3 KPa and a drying time of 4.5 hours.
[0068] In step (4), the frequency of ultrasonic dispersion is 20 kHz.
[0069] The composite material of this embodiment is used for preventing peritoneal dialysis catheter outlet infection in the preparation of peritoneal dialysis catheter. Figure 1~Figure 2 As shown, the peritoneal dialysis catheter comprises an implant tube, and the implant tube comprises an intra-abdominal section 1, a subcutaneous section 2 and an exposed section 3, wherein the intra-abdominal section 1 and the exposed section 3 are respectively connected to the two ends of the subcutaneous section 2, and the exposed section 3 is connected to a connector 4 at one end away from the subcutaneous section 2; an inner cuff 5 is provided at one end of the subcutaneous section 2 close to the intra-abdominal section 1, and an outer cuff 6 is provided at one end of the subcutaneous section 2 close to the exposed section 3; an outer surface of the implant tube between the outer cuff 6 and the connector 4 and an outer surface of the connector 4 are covered with an antibacterial coating 7; the antibacterial coating 7 is made of Cu 2+ / TA / HAP / CS composite material.
[0070] The method for obtaining the antibacterial coating 7 on the outer surface of the connector 4 is as follows: a stainless steel cylindrical ring is used as an anode and a titanium alloy sheet is used as a cathode. 2+ / TA / HAP / CS composites were deposited by EPD solution at 20 V DC for 5 min;
[0071] The method for obtaining the antibacterial coating 7 on the outer surface of the insertion tube is as follows:
[0072] Cu 2+ The EPD solution of the / TA / HAP / CS composite material was coated and dried in an oven at 38°C for 10 h.
[0073] Example 3
[0074] A method for preparing a composite material for preventing peritoneal dialysis catheter outlet infection comprises the following steps:
[0075] Step (1), preparation of TA / HAP NPs nanoparticles: adding hydroxyapatite to a 5 mg / mL tannic acid aqueous solution, reacting under centrifugal conditions, removing the supernatant after the reaction, and then drying to obtain TA / HAP NPs nanoparticles;
[0076] The mass ratio of hydroxyapatite to the volume ratio of tannic acid aqueous solution is 2:52 g / mL;
[0077] Step (2), Cu 2+ Preparation of / TA / HAP composite material: Add the TA / HAP NPs prepared in step (1) to a 5 mg / mL copper chloride dihydrate aqueous solution, react under centrifugal conditions, remove the supernatant after the reaction, and then dry to obtain Cu 2+ / TA / HAP composites;
[0078] Among them, the volume ratio of the mass of TA / HAP NPs nanoparticles to the cupric chloride dihydrate aqueous solution was 2:52 g / mL;
[0079] Step (3), preparation of chitosan acetic acid aqueous solution: uniformly mixing acetic acid aqueous solution with a volume percentage concentration of 1% and chitosan aqueous solution with a mass percentage concentration of 1% to obtain chitosan acetic acid aqueous solution;
[0080] The volume ratio of the acetic acid aqueous solution to the chitosan aqueous solution is 9.3:1;
[0081] Step (4), Cu 2+ Preparation of / TA / HAP / CS composites: Cu 2+ The / TA / HAP composite material was added to the chitosan acetic acid aqueous solution obtained in step (3) and ultrasonically dispersed to obtain Cu 2+ / TA / HAP / CS composite EPD solution;
[0082] Among them, Cu 2+ The volume ratio of the mass of / TA / HAP composite material to chitosan acetate aqueous solution was 1.05:1 mg / mL.
[0083] In step (1), the centrifugal speed is 10000 rpm, and the centrifugal time is 10 min; the drying is carried out by vacuum drying, the drying temperature is 70° C., the vacuum degree is 98.6 KPa, and the time is 5.5 hours.
[0084] In step (2), the centrifugal speed is 10000 rpm, and the centrifugal time is 10 min. Vacuum drying is adopted, the drying temperature is 70° C., the vacuum degree is 98.6 KPa, and the time is 5.5 hours.
[0085] In step (4), the frequency of ultrasonic dispersion is 100 kHz.
[0086] The composite material of this embodiment is used for preventing peritoneal dialysis catheter outlet infection in the preparation of peritoneal dialysis catheter. Figure 1~Figure 2 As shown, the peritoneal dialysis catheter comprises an implant tube, and the implant tube comprises an intra-abdominal section 1, a subcutaneous section 2 and an exposed section 3, wherein the intra-abdominal section 1 and the exposed section 3 are respectively connected to the two ends of the subcutaneous section 2, and the exposed section 3 is connected to a connector 4 at one end away from the subcutaneous section 2; an inner cuff 5 is provided at one end of the subcutaneous section 2 close to the intra-abdominal section 1, and an outer cuff 6 is provided at one end of the subcutaneous section 2 close to the exposed section 3; an outer surface of the implant tube between the outer cuff 6 and the connector 4 and an outer surface of the connector 4 are covered with an antibacterial coating 7; the antibacterial coating 7 is made of Cu 2+ / TA / HAP / CS composite material.
[0087] The method for obtaining the antibacterial coating 7 on the outer surface of the connector 4 is as follows: a stainless steel cylindrical ring is used as an anode and a titanium alloy sheet is used as a cathode. 2+ / TA / HAP / CS composites were deposited by EPD solution at 20 V DC for 7 min;
[0088] The method for obtaining the antibacterial coating 7 on the outer surface of the insertion tube is as follows:
[0089] Cu 2+ The EPD solution of the / TA / HAP / CS composite material was coated and dried in an oven at 42°C for 12 h.
[0090] Example 4
[0091] A method for preparing a composite material for preventing peritoneal dialysis catheter outlet infection comprises the following steps:
[0092] Step (1), preparation of TA / HAP NPs nanoparticles: adding hydroxyapatite to a 5 mg / mL tannic acid aqueous solution, reacting under centrifugal conditions, removing the supernatant after the reaction, and then drying to obtain TA / HAP NPs nanoparticles;
[0093] The mass ratio of hydroxyapatite to the volume ratio of tannic acid aqueous solution is 2:50 g / mL;
[0094] Step (2), Cu 2+Preparation of / TA / HAP composite material: Add the TA / HAP NPs prepared in step (1) to a 5 mg / mL copper chloride dihydrate aqueous solution, react under centrifugal conditions, remove the supernatant after the reaction, and then dry to obtain Cu 2+ / TA / HAP composites;
[0095] Among them, the volume ratio of the mass of TA / HAP NPs nanoparticles to the cupric chloride dihydrate aqueous solution was 2:50 g / mL;
[0096] Step (3), preparation of chitosan acetic acid aqueous solution: uniformly mixing acetic acid aqueous solution with a volume percentage concentration of 1% and chitosan aqueous solution with a mass percentage concentration of 1% to obtain chitosan acetic acid aqueous solution;
[0097] The volume ratio of the acetic acid aqueous solution to the chitosan aqueous solution is 9:1;
[0098] Step (4), Cu 2+ Preparation of / TA / HAP / CS composites: Cu 2+ The / TA / HAP composite material was added to the chitosan acetic acid aqueous solution obtained in step (3) and ultrasonically dispersed to obtain Cu 2+ / TA / HAP / CS composite EPD solution;
[0099] Among them, Cu 2+ The volume ratio of the mass of / TA / HAP composite material to the chitosan acetate aqueous solution was 1:1 mg / mL.
[0100] In step (1), the centrifugal speed is 95000 rpm, and the centrifugal time is 10 min; the drying is carried out by vacuum drying, the drying temperature is 70° C., the vacuum degree is 95 KPa, and the time is 5 hours.
[0101] In step (2), the centrifugal speed is 95000 rpm, and the centrifugal time is 10 min. Vacuum drying is adopted, the drying temperature is 70° C., the vacuum degree is 96 KPa, and the time is 5 hours.
[0102] In step (4), the frequency of ultrasonic dispersion is 80 kHz.
[0103] The composite material of this embodiment is used for preventing peritoneal dialysis catheter outlet infection in the preparation of peritoneal dialysis catheter. Figure 1~Figure 2As shown, the peritoneal dialysis catheter comprises an implant tube, and the implant tube comprises an intra-abdominal section 1, a subcutaneous section 2 and an exposed section 3, wherein the intra-abdominal section 1 and the exposed section 3 are respectively connected to the two ends of the subcutaneous section 2, and the exposed section 3 is connected to a connector 4 at one end away from the subcutaneous section 2; an inner cuff 5 is provided at one end of the subcutaneous section 2 close to the intra-abdominal section 1, and an outer cuff 6 is provided at one end of the subcutaneous section 2 close to the exposed section 3; an outer surface of the implant tube between the outer cuff 6 and the connector 4 and an outer surface of the connector 4 are covered with an antibacterial coating 7; the antibacterial coating 7 is made of Cu 2+ / TA / HAP / CS composite material.
[0104] The method for obtaining the antibacterial coating 7 on the outer surface of the connector 4 is as follows: a stainless steel cylindrical ring is used as an anode and a titanium alloy sheet is used as a cathode. 2+ / TA / HAP / CS composites were deposited by EPD solution at 20 V DC for 6 min;
[0105] The method for obtaining the antibacterial coating 7 on the outer surface of the insertion tube is as follows:
[0106] Cu 2+ The EPD solution of the / TA / HAP / CS composite material was coated and dried in an oven at 40°C for 11 h.
[0107] Example 5
[0108] like Figure 1~Figure 2 As shown, a peritoneal dialysis catheter comprises an implant tube, wherein the implant tube comprises an intra-abdominal section 1, a subcutaneous section 2 and an exposed section 3, wherein the intra-abdominal section 1 and the exposed section 3 are respectively connected to two ends of the subcutaneous section 2, and an end of the exposed section 3 away from the subcutaneous section 2 is connected to a connector 4; an end of the subcutaneous section 2 close to the intra-abdominal section 1 is provided with an internal cuff 5, and an end of the subcutaneous section 2 close to the exposed section 3 is provided with an external cuff 6; an outer surface of the implant tube between the external cuff 6 and the connector 4 and an outer surface of the connector 4 are covered with an antibacterial coating 7; the antibacterial coating 7 is made of the Cu described in Example 1 2+ / TA / HAP / CS composite material.
[0109] Example 6
[0110] like Figure 1~Figure 2 As shown, a peritoneal dialysis catheter comprises an implant tube, wherein the implant tube comprises an intra-abdominal section 1, a subcutaneous section 2 and an exposed section 3, wherein the intra-abdominal section 1 and the exposed section 3 are respectively connected to two ends of the subcutaneous section 2, and an end of the exposed section 3 away from the subcutaneous section 2 is connected to a connector 4; an end of the subcutaneous section 2 close to the intra-abdominal section 1 is provided with an internal cuff 5, and an end of the subcutaneous section 2 close to the exposed section 3 is provided with an external cuff 6; an outer surface of the implant tube between the external cuff 6 and the connector 4 and an outer surface of the connector 4 are covered with an antibacterial coating 7; the antibacterial coating 7 adopts the Cu described in Example 42+ / TA / HAP / CS composite material.
[0111] The material of the connector is titanium.
[0112] Performance testing:
[0113] (1) Cu 2+ / TA / HAP / CS composite coating antibacterial performance test:
[0114] The samples are bare Ti alloy sheet, Ti alloy sheet with CS coating, and Ti alloy sheet with Cu 2+ / TA / HAP / CS composite coatings are named Ti alloy group, Ti-CS group, and Ti-CS@NP group, respectively.
[0115] The Ti alloy sheet with CS coating is obtained by using a stainless steel cylindrical ring as an anode and a titanium alloy sheet as a cathode, and depositing the chitosan acetic acid aqueous solution obtained in step (3) at a DC voltage of 20 V for 5 min.
[0116] With Cu 2+ The Ti alloy sheet of the / TA / HAP / CS composite material coating is obtained by step (4) 2+ The EPD solution of the / TA / HAP / CS composite material was coated on a Ti alloy sheet using the EPD method.
[0117] The bare Ti alloy sheet is a Ti alloy sheet without any coating.
[0118] Ti alloy sheet with CS coating, Cu 2+ The coating thickness of the Ti alloy sheets coated with / TA / HAP / CS composite materials was 0.3 μm;
[0119] (1.1) The antibacterial properties of the coating were tested using standard plate counting techniques.
[0120] 1) After UV sterilization of the sample for 30 minutes, immerse the sample vertically in the prepared bacterial solution and culture it in a shaker in a 37°C constant temperature incubator for 12 to 14 hours. The shaking speed is 120 rpm;
[0121] The bacterial solution is LB culture medium containing Escherichia coli or LB culture medium containing Staphylococcus aureus, and the bacterial concentrations of Escherichia coli and Staphylococcus aureus are 10 8 cells / mL (measured by microplate reader at 540 nm wavelength);
[0122] The formula of the LB medium is: 10 g of tryptone, 5 g of yeast powder, 10 g of tryptophan, 10 g of NaCl, and 1 L of water.
[0123] 2) After incubation, wash three times with 0.9wt% sodium chloride solution to remove non-adherent bacteria.
[0124] 3) Each sample was ultrasonicated in 10 mL of 0.9 wt% sodium chloride solution for 30 min to release the adhered bacterial cells and obtain a bacterial solution.
[0125] 4) Take 100 μL of bacterial solution and dilute it 10, 100, and 1000 times respectively.
[0126] 5) 100 μL of the diluted bacterial solution was distributed on the agar plate and incubated at 37 °C for 24 h, after which photos of the colonies growing on the agar plate were taken.
[0127] The formula of agar plate is: 10g tryptone, 5g yeast powder, 10g tryptophan, 10g NaCl, and 1L deionized water.
[0128] (1.2) The bacterial dispersion on the composite coating was determined using live and dead bacteria staining techniques
[0129] The samples were placed in a 96-well plate, and 200 μL of Escherichia coli suspension (10 8 CFU / mL, PBS) or Staphylococcus aureus suspension (10 8 CFU / mL, PBS). After incubation at 37°C for 10 h, the samples were gently rinsed with 0.9wt% sodium chloride solution and then treated with a mixture of SYTO 9 (final concentration of 6µmol / L) and PI (final concentration of 30µmol / L) (L7012 kit) for 10 min. After treatment, the samples were observed and images were captured using an upright fluorescence microscope (Nikon 80i, Japan). The antibacterial activity of the coatings was studied using standard plate counts and live and dead staining.
[0130] (1.3) Result analysis
[0131] 1) Figure 3 (a)- Figure 3 (h) shows the antibacterial performance test results of the coating using the plate colony counting method. The results are the test results of the bacterial solution diluted 1000 times in 4) of (1.1);
[0132] In the Ti alloy group, the number of E. coli colonies on the agar plate was large, e.g. Figure 3 As shown in (a), it shows that the antibacterial effect of bare Ti alloy is very small.
[0133] Compared with the Ti alloy group, the number of colonies in the Ti-CS group on the agar plate was significantly reduced, e.g. Figure 3As shown in (b), it is significantly reduced, indicating that the CS coating has certain antibacterial properties.
[0134] The number of colonies on the agar plate of the Ti-CS@NP group was further reduced, e.g. Figure 3 (c) shows that Cu 2+ / TA / HAP / CS composite coating has good antibacterial properties against Escherichia coli.
[0135] Quantitative evaluation of E. coli colonies, such as Figure 3 As shown in (d), the results show that the Ti-CS@NP group has the least E. coli colonies, indicating that the corresponding coating has good antibacterial properties against E. coli.
[0136] 2) According to Figure 3 (e)- Figure 3 (h), we can conclude that the Ti-CS@NP group also has strong antibacterial activity against Staphylococcus aureus. These results show that the coating used in the Ti-CS@NP group has good overall antibacterial properties.
[0137] Specifically, in the Ti alloy group, the number of Staphylococcus aureus colonies on the agar plate was large, e.g. Figure 3 As shown in (e), it shows that the antibacterial effect of bare Ti alloy is very small.
[0138] Compared with the Ti alloy group, the number of colonies in the Ti-CS group on the agar plate was significantly reduced, e.g. Figure 3 As shown in (f), it is significantly reduced, indicating that the CS coating has certain antibacterial properties.
[0139] The number of colonies on the agar plate of the Ti-CS@NP group was further reduced, e.g. Figure 3 (g) shows that Cu 2+ / TA / HAP / CS composite coating has good antibacterial properties against Staphylococcus aureus.
[0140] Quantitative evaluation of Staphylococcus aureus colonies, such as Figure 3 As shown in (h), the results show that the Ti-CS@NP group has the least Staphylococcus aureus colonies, indicating that the corresponding coating has good antibacterial properties against Staphylococcus aureus.
[0141] 3) To further study the antibacterial properties of the coating, live and dead bacteria staining techniques were used. Live bacteria were stained with SYTO 9 to show green fluorescence, while dead bacteria were stained with PI to show red (e.g. Figure 4). A large number of live bacteria were found on the bare Ti alloy, while few dead bacteria were found. Compared with the bare Ti alloy, the number of live bacteria on the Ti-CS@NP group was significantly reduced, while the number of dead bacteria was significantly increased. These observations support the conclusion that the coatings used in the Ti-CS@NP group have good antibacterial properties.
[0142] (2) Cu 2+ Cytotoxicity test of / TA / HAP / CS composite coating
[0143] Cu 2+ It has a good antibacterial effect. It can combine with sulfhydryl groups, change the permeability of bacterial cell membranes, produce reactive oxygen species, oxidize bacterial proteins, degrade DNA, and cause bacterial death. In addition, Cu 2+ It can interfere with cell division and replication, thereby affecting bacterial DNA synthesis. 2+ It can also change the structure and function of bacterial cell wall proteins, causing cell rupture. 2+ It has bactericidal effect, but can also cause damage to cells. Therefore, it is necessary to verify the cytotoxicity of the synthesized coating.
[0144] FDA and PI were used for live and dead bacteria staining. Briefly, MC3T3-E1 cells (mouse embryonic osteoblast precursor cells) were cultured at 5 × 10 4 The cells were planted on a 24-well culture plate on the sample at a density of 10 cells / well, cultured in LB medium, and shaken in a constant temperature incubator at 37°C and 120 rpm for 48 hours. Then, 5 mg of fluorescein diacetate (FDA) was added to 1 ml of acetone, dissolved and mixed, and used as a live cell stain to stain live cells; 1 mg of propidium iodide (PI) was added to 1 ml of phosphate buffered saline, dissolved and mixed, and used as a dead cell stain to stain dead cells.
[0145] Finally, an upright fluorescence microscope (Nikon 80i, Japan) was used to observe and record the cell adhesion morphology and the ratio of live and dead cells on the sample surface. The number of live cells and the total coverage area were used to quantitatively characterize the cytotoxicity of the coating. FDA-labeled live cells showed green fluorescence, while PI-labeled dead cells showed red fluorescence, as shown in Figure 2. Figure 5 The results show that compared with the bare Ti alloy sheet and the Ti alloy sheet with CS coating, the surface of the Ti alloy sheet with Cu 2+ The cell morphology on the Ti alloy sheet surface of the / TA / HAP / CS composite coating is better diffused and shows more platelet foot extension, indicating that the Cu 2+ / TA / HAP / CS composite coating has better cell compatibility.
[0146] According to the red fluorescence images, there are only a few scattered dead cells on the surface of the bare Ti alloy sheet, while on the Ti alloy sheet with CS coating and Cu 2+ Almost no dead cells were observed on the surface of Ti alloy sheets coated with / TA / HAP / CS composites. These results indicate that the CS coating and Cu 2+ / TA / HAP / CS coated Ti alloy sheet is less harmful to cells. 2+ / TA / HAP / CS coating has low cytotoxicity and good cell compatibility. The number of living cells on the surface of bare Ti alloy sheet, the number of living cells on Ti alloy sheet with CS coating, and the number of living cells on Ti alloy sheet with Cu 2+ The number of viable cells of Ti alloy sheets with / TA / HAP / CS composite coatings increases in turn. 2+ The number of cells on the surface of the Ti alloy sheet coated with the / TA / HAP / CS composite material is almost 1.9 times that of the bare Ti alloy sheet, which is similar to the fluorescence image, proving that Cu 2+ / TA / HAP / CS composite coating has little cytotoxicity. 2+ The overall cell coverage area on the surface of the Ti alloy sheet coated with the / TA / HAP / CS composite was twice that of the bare Ti alloy sheet, indicating that the coating had better cell compatibility.
[0147] (3) Scanning electron microscope Cu 2+ / TA / HAP / CS composite coating
[0148] By scanning electron microscopy, we can see the growth of MC3T3-E1 cells (mouse embryonic osteoblast precursor cells) on the sample surface (e.g. Figure 6 ).
[0149] Among them, the cells on the bare Ti alloy sheet surface had poor curling and spreading, indicating poor cell compatibility. The cells on the Ti alloy sheet surface with CS coating showed the extension of lamellar feet, which was better than the cell spreading of the bare Ti alloy sheet. 2+ On the Ti alloy sheet surface coated with / TA / HAP / CS composites, cells showed more lamellar foot extension and more cells adhered to the surface, which indicated that the Cu 2+ / TA / HAP / CS composite coating promotes cell adhesion and migration. 2+ / TA / HAP / CS composite coating has good cell compatibility. Compared with bare Ti alloy sheet, 2+ / TA / HAP / CS composite coatings have more cell adhesion on the surface of Ti alloy sheets (e.g. Figure 7 ).
[0150] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a composite material for preventing peritoneal dialysis catheter outlet infection, characterized in that: The steps include: Step (1), preparation of TA / HAP NPs nanoparticles: adding hydroxyapatite to a 5 mg / mL tannic acid aqueous solution, reacting under centrifugal conditions, removing the supernatant after the reaction, and then drying to obtain TA / HAP NPs nanoparticles; The mass ratio of hydroxyapatite to the volume ratio of tannic acid aqueous solution is 2:48~52g / mL; Step (2), Cu 2+ Preparation of / TA / HAP composite material: Add the TA / HAP NPs prepared in step (1) to a 5 mg / mL copper chloride dihydrate aqueous solution, react under centrifugal conditions, remove the supernatant after the reaction, and then dry to obtain Cu 2+ / TA / HAP composites; Among them, the volume ratio of the mass of TA / HAP NPs nanoparticles to the cupric chloride dihydrate aqueous solution was 2:48~52g / mL; Step (3), preparation of chitosan acetic acid aqueous solution: uniformly mixing acetic acid aqueous solution with a volume percentage concentration of 1% and chitosan aqueous solution with a mass percentage concentration of 1% to obtain chitosan acetic acid aqueous solution; The volume ratio of the acetic acid aqueous solution to the chitosan aqueous solution is 8.7-9.3:1; Step (4), Cu 2+ Preparation of / TA / HAP / CS composites: Cu 2+ The / TA / HAP composite material was added to the chitosan acetic acid aqueous solution obtained in step (3) and ultrasonically dispersed to obtain Cu 2+ / TA / HAP / CS composite EPD solution; Among them, Cu 2+ The volume ratio of the mass of / TA / HAP composite material to chitosan acetate aqueous solution is 0.95~1.05:1 mg / mL.
2. The method for preparing a composite material for preventing peritoneal dialysis catheter outlet infection according to claim 1, characterized in that: In step (1), the centrifugal speed is 9000-10000 rpm, and the centrifugal time is 10 min; the drying is performed by vacuum drying, the drying temperature is 70° C., the vacuum degree is 93.3-98.6 kPa, and the time is 4.5-5.5 hours.
3. The method for preparing a composite material for preventing peritoneal dialysis catheter outlet infection according to claim 1, characterized in that: In step (2), the centrifugal speed is 9000-10000 rpm, and the centrifugal time is 10 min. Vacuum drying is adopted, the drying temperature is 70° C., the vacuum degree is 93.3-98.6 kPa, and the time is 4.5-5.5 hours.
4. The method for preparing a composite material for preventing peritoneal dialysis catheter outlet infection according to claim 1, characterized in that: In step (4), the frequency of ultrasonic dispersion is 20 kHz to 100 kHz.
5. The composite material for preventing peritoneal dialysis catheter outlet infection obtained by the preparation method of the composite material for preventing peritoneal dialysis catheter outlet infection according to any one of claims 1 to 4.
6. Use of the composite material for preventing peritoneal dialysis catheter outlet infection according to claim 5 in the preparation of peritoneal dialysis catheters.
7. Use of the composite material for preventing peritoneal dialysis catheter outlet infection according to claim 6 in the preparation of a peritoneal dialysis catheter, wherein the peritoneal dialysis catheter comprises an implantation tube, the implantation tube comprises an intra-abdominal section, a subcutaneous section and an exposed section, the intra-abdominal section and the exposed section are respectively connected to two ends of the subcutaneous section, and a joint is connected to an end of the exposed section away from the subcutaneous section; an end of the subcutaneous section close to the intra-abdominal section is provided with an internal cuff, and an end of the subcutaneous section close to the exposed section is provided with an external cuff; characterized in that The outer surface of the insertion tube from the outer cuff to the joint and the outer surface of the joint are covered with an antibacterial coating; the antibacterial coating is made of Cu 2+ / TA / HAP / CS composite material.
8. Use of the composite material for preventing peritoneal dialysis catheter outlet infection according to claim 7 in the preparation of a peritoneal dialysis catheter, characterized in that: The method for obtaining the antibacterial coating on the outer surface of the joint is as follows: a stainless steel cylindrical ring is used as the anode and a titanium alloy sheet is used as the cathode. 2 + The EPD solution of / TA / HAP / CS composites was deposited at 20 V DC voltage for 5–7 min; The method for obtaining the antibacterial coating on the outer surface of the insertion tube is as follows: Cu 2+ After coating with the EPD solution of the / TA / HAP / CS composite material, the composite material was dried in an oven at 38°C~42°C for 10~12h.
9. A peritoneal dialysis catheter, comprising an insertion tube, the insertion tube comprising an intra-abdominal section, a subcutaneous section and an exposed section, the intra-abdominal section and the exposed section are respectively connected to two ends of the subcutaneous section, and the exposed section is connected to a joint at one end away from the subcutaneous section; an end of the subcutaneous section close to the intra-abdominal section is provided with an internal cuff, and an end of the subcutaneous section close to the exposed section is provided with an external cuff; characterized in that: The outer surface of the insertion tube from the outer cuff to the joint and the outer surface of the joint are covered with an antibacterial coating; the antibacterial coating is made of Cu prepared by the preparation method of the composite material for preventing peritoneal dialysis catheter outlet infection according to any one of claims 1 to 4 2+ / TA / HAP / CS composite material.
10. The peritoneal dialysis catheter according to claim 9, characterized in that The material of the connector is titanium.
